An investigation on prospective German language teachers‟ autonomous learning level - (:unkn) unknown (My University, 2018)
Developments in the last decades necessitated the acquirement of diverse skills that enables to keep up with thechanging conditions of todays‟ world. In this context teachers as learners are in need of a continuous renewal.The acquirement of autonomous learning skills promoted at the teacher education might be contributory for thedevelopment of a lifelong learning ability. The aim of this study is to analyze the factors affecting theautonomous learning behaviors of prospective German language teachers to determine their actual state. Thusthe purpose of the study is to identify students‟ autonomous learning behaviors in view of different variables andto discuss the results with respect of learner autonomy and foreign language teacher education. For datacollection Autonomous Learning Scale was developed and used. Nonparametric Kruskal - Wallis and Mann -Whitney U tests were used to identify whether there is a significant difference between students autonomouslearning behaviors according to class, age, gender and educational background. The results of the study showedthat there is no statistical significant difference among class level and educational background in terms ofautonomous learning, but there were statistical significant differences with regards of age and gender. Further thesubscales „planning‟ and „performing‟ had on average a higher score as the subscale „evaluating‟. The findingsof the study indicated that teachers as learners have to be promoted with regard to their actual state. Furtherstudies regarding learner autonomy in teacher education are recommended for the promotion of teachercompetences.

Günümüz dünyasında yaşanan gelişmeler farklı bilgi ve becerilerin edinilmesini zorunlu kılmıştır. Bu bağlamda birer öğrenen olarak öğretmenlerin de bilgi ve becerilerini günün gerektirdiği düzeye getirmeleri gerekmektedir. Özerk öğrenme becerisi ise bu konuda yardımcı olabileceği düşünülmektedir. Bu çalışma, aday Almanca öğretmenlerinin özerk öğrenme düzeylerini çeşitli değişkenler açısından incelemek amacıyla yapılmıştır. Veriler, Alman Dili Eğitimi Anabilim Dalında eğitim gören öğrencilerden toplanmıştır. Bu çalışma, aday Almanca öğretmenlerinin özerk öğrenme düzeyleri ile yaş ve cinsiyet arasında bir farklılığın olduğunu göstermiştir. Öğrenmenin planlama, uygulama ve değerlendirme aşamalarında da yaş ve cinsiyet açısından farklılıkların olduğunu göstermiştir.
Almanca öğretmeni adaylarının özerk öğrenme düzeylerine ilişkin bir inceleme
Keywords: Dil ve Dil Bilim